(untitled) (Sirte University Journal of Humanities, 2026)
study evaluates the role of the Libyan legislative framework in protecting marine resources and its impact on the economic value of marine projects from an accounting perspective, with emphasis on transparency and financial disclosure in supporting sustainability and decision-making. The findings indicate that national laws, particularly Law No. 14 of 1989 and Environmental Protection Law No. 15 of 2003, along with international agreements such as the United Nations Convention on the Law of the Sea, contribute to limiting the overexploitation of marine resources, preserving fish stocks, coral reefs, and marine minerals, and reducing losses caused by unregulated fishing activities. The study further demonstrates that integrating legal frameworks with environmental accounting, and recognizing marine resources as natural assets within financial statements, enhances transparency and accountability while providing reliable data for assessing the economic value of marine assets. The application of the Legal-Accounting Impact Model enabled the measurement of the impact of legislation on net economic value by linking it to compliance costs and environmental losses, thereby confirming the effectiveness of integrating law and accounting in supporting the blue economy. The results also show that weak enforcement mechanisms and limited environmental disclosure practices reduce the ability to accurately assess the economic performance of marine projects. Accordingly, the study recommends updating national legislation, strengthening environmental and financial disclosure systems in line with ESG indicators, improving monitoring and enforcement capacity, and expanding regional cooperation through initiatives such as the WestMED Initiative. The study concludes that integrating legal frameworks with environmental accounting and financial transparency represents a key supporting pillar for enhancing the economic value of marine resources, diversifying the Libyan economy, and achieving sustainable development goals, particularly Sustainable Development Goal 14 on Life Below Water.